Educational Status Hierarchies, After-School Activities, and Parenting Logics: Lessons from Canada. Issue 2 (April 2020) - Aurini, Janice; Missaghian, Rod; Milian, Roger Pizarro
This article draws from American research on ''concerted cultivation'' to compare the parenting logics of 41 upper-middle-class parents in Toronto, Canada. We consider not only how parents structure their children's after-school time (what parents do) but also how the broader ecology of schooling informs their parenting logics (how they rationalize their actions). We find that parenting practices mirror American research. Upper-middle-class families enroll their children in multiple lessons and cultivate their children's skills. However, unlike their American counterparts, Canadian parenting logics are not explicitly stratification oriented, guided by a desire to access elite universities. Canada's relatively flat stratification system of higher education, where prestige differences between universities are minimal, prompts the emergence of a more expressive parenting ethos. Our findings draw attention to the macrofoundations of social behavior by articulating the connection between parenting logics and educational status hierarchies. We conclude by considering the implications of cross-national differences to theories of parenting and social stratification.